2023
DOI: 10.1371/journal.pone.0291835
|View full text |Cite
|
Sign up to set email alerts
|

The application of enhanced recovery after surgery (ERAS) in chronic rhinosinusitis patients undergoing endoscopic sinus surgery: A systematic review and meta-analysis

Yuqi Wu,
Yijie Fu,
Yuanqiong He
et al.

Abstract: Objectives Enhanced recovery after surgery (ERAS) has become extensively practiced and has shown encouraging benefits. Within recent years, ERAS has also been increasingly performed in chronic rhinosinusitis (CRS) patients undergoing endoscopic sinus surgery (ESS). However, the actual efficacy of ERAS in CRS patients undergoing ESS is not completely clear, and the related evidence remains weak. This systematic review and meta-analysis aimed to evaluate the effectiveness and safety of ERAS in the perioperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Previous research has shown that there are differences between patients in terms of bleeding rates, pain, and postoperative recovery quality between different types of tonsillectomy 29 , 56 . Furthermore, a significant amount of literature validates the idea that improved recovery after surgery (ERAS) protocols and similar approaches can reduce postoperative pain, anxiety, and depression, thus improving quality of life 57 - 59 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous research has shown that there are differences between patients in terms of bleeding rates, pain, and postoperative recovery quality between different types of tonsillectomy 29 , 56 . Furthermore, a significant amount of literature validates the idea that improved recovery after surgery (ERAS) protocols and similar approaches can reduce postoperative pain, anxiety, and depression, thus improving quality of life 57 - 59 .…”
Section: Discussionmentioning
confidence: 95%